Estrategias para el desarrollo socio – afectivo en estudiantes con problemas de conducta en el área de lengua y literatura, bloque 6 rimas del quinto grado de educación general básica paralelo B, de la escuela de educación básica Dra. Matilde Hidalgo de Procel n° 1 de la ciudad de Loja, período lectivo 2013 – 2014 - Siguenza Erreyes, Johanna Elizabeth (2015)
The investigative work entitled: strategies for socio – affective development in students with behavioral problems in the areas of language and literature, block 6 rimes parallel fifth grade B, of General Basic Education Dra. Matilde Hidalgo de Prcoel N°1 school of Loja city, academic period 2013 – 2014, it has set a goal generalde researching this topic: Determine the use of alternative strategies to be implemented by the educator to promote socio - emotional development of estudents with behavioral problems according to the behavior evidenced in the academis proccess. The present research is experimental, it was neccesary the use of the following methods: Comprehensive method, analytical method, comprensive evaluation method; almost experimental and investigate process for the use of these methods was necessary. Besides the tecnique of direct observation and survey which the teacher and students participated was used. The result being that students have no knowledge referred to socio – emotional development and the consequences for behavior problems, also confuse the affection they get from their parents and teacher, such as activities that promote socio – emotional development. In the research work involved 30 human talents: 29 students and the teacher in charge of fifth grade, parallel “B” of General Basic Education “Dra. Matilde Hidalgo de Procel N° 1 School”. For the above it is concluded that the use of strategies to promote socio emotional development contribute the students.